Geochemical Characteristics of Host Rocks of Polymetalic Ephitermal Quartz Veins at Soripesa Prospect Area, Sumbawa Island, Indonesia - Khant, Win (2012)
The Soripesa prospect area is located at Maria village, Wawo district, Bima region in the eastern part of Sumbawa Island, Indonesia. This area is a part of Cenozoic Calc-alkaline volcanic inner Banda-Sunda Arc. There have five main polymetallic epithermal quartz veins in the Soripesa prospect area, namely, Rini vein, Jambu air vein, Dollah vein, Merpati vein, and Arif vein. The dominant lithology is a lithic-crystal tuff of andesitic and dacitic composition and bedded limestone. Major oxidesand trace elementswere analysedusing X-Ray Fluorescence (XRF)to identify the host rock geochemistry. The main veins are hostedbyandesitic and andesitic/basaltic volcanic host rocks. Major elementscompositions are affected by alteration.Based on the trace element data, host rocksofall veins were formed inthe volcanic arc basalt (VAB) and island arc basalt (IAB)tectonic setting.Host rocks of Rini vein contain higher amount of precious and base metal elements (Zn, Cu, Pb, and Ag.etc.) than those ofother host rocks.